1994
DOI: 10.1017/s0898588x00001279
|View full text |Cite
|
Sign up to set email alerts
|

Ideas, Institutions, and Policy Patterns: Hardrock Mining, Forestry, and Grazing Policy on United States Public Lands, 1870–1985

Abstract: From the mid–1800s through the mid–1980s, the federal government initiated programs to manage three types of resources on the lands that it controlled. The discovery of gold in California and elsewhere in the West prompted the first government policy in the 1860s. Debate over the nation's forests began in the 1870s, and a system of national forests to be managed by a federal Forest Service was created in the late 1800s and early 1900s. And in the 1930s, the government finally began to manage the lands no one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Stone (1989) has observed that the norms of political regimes affect the political agendas of cities, e.g., by legitimizing cooperation between African-American politicians and downtown business interests. Some policy domains can be said to have embedded norms about the proper role of government versus private interests, such as in determining the private use of public lands for grazing, forestry, and mining (Klyza 1994).…”
Section: Neopluralism and The Two Faces Of Powermentioning
confidence: 99%
“…Stone (1989) has observed that the norms of political regimes affect the political agendas of cities, e.g., by legitimizing cooperation between African-American politicians and downtown business interests. Some policy domains can be said to have embedded norms about the proper role of government versus private interests, such as in determining the private use of public lands for grazing, forestry, and mining (Klyza 1994).…”
Section: Neopluralism and The Two Faces Of Powermentioning
confidence: 99%